Missense variants of FBN2 associated with congenital arachnodactyly in three Chinese families - Yu Sui; Yongping Lu; Meina Lin; Xinren Chen; Xiang Ni; Huan Li; Miao Jiang (Molecular Genetics and Metabolism Reports)
Background: Congenital contractural arachnodactyly (CCA) is a rare autosomal dominant disorder caused by pathogenic variants of Fibrillin-2 (FBN2) gene. This study aimed to investigate the variants in three Chinese families with CCA. Methods: Next-generation sequencing analysis and Sanger sequencing of exons 24–35 of FBN2 (NM_001999.4) were performed on the three CCA pedigrees. The pathogenicity of the variants was assessed using ACMG criteria and predicted using an in-silico program. Results: A novel heterozygous substitution (NM_001999.4: c.3230G > A; NP_001990.2 p. Cys1077Tyr) was identified in all patients from pedigree A, but not in healthy family members. The variant was found to be pathogenic. Additionally, in pedigree B (NM_001999.4: c.4222G > A; NP_001990.2: p.Asp1408Asn) and C (NM_001999.4: c.3170G > A; NP_001990.2: p.Gly1057Asp), and the previously reported variants were detected. Variants affecting cysteine residues may disrupt disulfide bridging, leading to a weakened microfibril scaffold, resulting in CCA phenotypes. High phenotypic heterogeneity was observed among different families, and there was little correlation between the genotype and phenotype. Conclusion: This study describes three large families with CCA caused by missense variants in the FBN2 gene. Phenotypic variations were observed among different pedigree groups, and further research is needed to investigate the underlying reasons for these variations.